The Clinical Review Committee: Impact of the Development of In Vitro Diagnostic Tests for SARS-CoV-2 Within RADx Tech - Matthew Robinson; Charlotte Gaydos; Barbara Van Der Pol; Sally McFall; Yu-Hsiang Hsieh; William Clarke; Robert L. Murphy; Lea E. Widdice; Lisa R. Hirschhorn; Richard Rothman; Chad Achenbach; Claudia Hawkins; et al. (IEEE Open Journal of Engineering in Medicine and Biology, 2021)
The NIH Rapid Acceleration of Diagnostics (RADxSM) Tech Program was created to speed the development, validation, and commercialization of innovative point-of-care (POC) and home-based tests, and to improve clinical laboratory tests, that can directly detect SARS-CoV-2. Leveraging the experience of the Point-of-Care Technologies Research Network, a Clinical Review Committee (CRC) composed of clinicians, bioengineers, regulatory experts, and laboratorians was created to provide structured feedback to SARS-CoV-2 diagnostic innovators. The CRC convened 53 meetings with 49 companies offering SARS-CoV-2 tests in POC and reference laboratory formats as well as collection materials. The CRC identified common barriers to device design finalization including biosafety, workflow, result reporting, regulatory requirements, sample type, supply chain, limit of detection, lack of relevant validation data, and price-performance-use mismatch. Feedback from companies participating was positive.